EVALUASI IMPLEMENTASI KURIKULUM MERDEKA DENGAN MODEL CIPP DI SEKOLAH MENENGAH KEJURUAN - Nurrahman, Arief; Saputri, Agatha; Nugraha, R. Andro Zylio; Juliani, Dian (Jurnal Al Burhan, 2023)
This research is evaluation research using the CIPP model which aims to evaluate the implementation of the Independent Curriculum in Vocational Schools especially in accounting majors with a focus on the achievements of context, input, process and product. The resource persons in this study consisted of school principals, deputy principals, teachers and students who were taken using purposive sampling techniques. Data collection techniques through observation, interviews and documentation. Analysis techniques. The data used is descriptive analysis. The research results show that: (1) Aspects evaluation of the curriculum implementation context in the form of suitability to school criteria, content standards, the school's vision, mission and goals are sufficient to support the implementation of the Independent Curriculum; (2) The input evaluation aspect in the form of readiness, understanding, preparation and infrastructure is quite ready even though there are components of facilities and infrastructure that need to be further optimized; (3) The evaluation process aspect in the form of implementing the Independent Curriculum has not been optimal because there are still teachers who still use old techniques in learning, have not implemented assessments, have not implemented the Pancasila Student Profile Strengthening Project, and the infrastructure is not yet optimal; (4) The product evaluation aspect of the implementation of the Independent Curriculum is quite good, seen from the positive impact provided in the form of increasing learning outcomes and student activity in learning as well as motivation and achievement in participating race. The conclusion from the research results is that the evaluation of the implementation of the Independent Curriculum in Vocational Schools is quite good because it can be seen from the increase in student learning outcomes. Apart from that, there are several recommendations such as mentoring, improving infrastructure, improving the quality of education, improving learning assessments, carrying out evaluations, and conducting needs analysis.